IMPORTANCE OF CONTEXTUAL DATA IN PRODUCING HEALTH TECHNOLOGY ASSESSMENT RECOMMENDATIONS: A CASE STUDY. (27th February 2018) - Poder, Thomas G.; Bellemare, Christian A.
Abstract : Objectives: Contextual data and local expertise are important sources of data that cannot be ignored in hospital-based health technology assessment (HTA) processes. Despite a lack of or unconvincing evidence in the scientific literature, technology can be recommended in a given context. We illustrate this using a case study regarding biplane angiography for vascular neurointervention. Methods: A systematic literature review was conducted, along with an analysis of the context in our setting. The outcomes of interest were radiation doses, clinical complications, procedure times, purchase cost, impact on teaching program, the confidence of clinicians in the technology, quality of care, accessibility, and the volume of activity. A committee comprising managers, clinical experts, physicians, physicists and HTA experts was created to produce a recommendation regarding biplane technology acquisition to replace a monoplane device. Results: The systematic literature review yielded nine eligible articles for analysis. Despite a very low level of evidence in the literature, the biplane system appears to reduce ionizing radiation and medical complications, as well as shorten procedure time. Contextual data indicated that the biplane system could improve operator confidence, which could translate into reduced risk, particularly for complex procedures. In addition, the biplane system can support our institution in its advanced procedures teaching program. Conclusions: Given the advantages provided by the biplane technology in our setting, the committee has recommended its acquisition. Contextual data were of utmost importance in this recommendation. Moreover, this technology should be implemented alongside a responsibility to collect outcome data to optimize clinical protocol in the doses of ionizing delivered.